Model Pembelajaran Statistika dengan Pendekatan Didaktik Digital - Deasy Wahyuni; Afifah Ainun Nadjla (Prosiding SISFOTEK, 2025)
This study develops a digital didactics-based statistics learning model to enhance students' 21st-century statistical abilities. Using the ADDIE framework, the research designed a model integrating pedagogical, technological, and social collaboration aspects. Expert validation yielded a high feasibility score of 4.65/5. Experimental implementation with 75 students showed significant improvements in conceptual understanding, digital tool proficiency with R, critical data thinking, and data ethics awareness compared to conventional methods. The model's novelty lies in its systematic integration of Digital Didactical Design with triple-focus learning outcomes and open-source platforms (RStudio Cloud, GitHub). Quantitative analysis revealed significant differences (p<0.05) between experimental and control groups, while qualitative findings demonstrated enhanced engagement and authentic learning experiences. The study concludes that transforming statistics education requires comprehensive learning ecology redesign rather than mere technological substitution, offering a practical framework for developing relevant digital-era statistical competencies.